The Analysis of Iron (Fe) Level In Alkaline Water in Makale District, Tana Toraja Regency - Hasanuddin, Asni; Jurnal Syarif (PT Inovasi Pratama Internasional, 2022)
Alkaline water is drinking water that can be drunk directly because it meets the requirements for drinking water quality. Alkaline water has a pH above 7 so this water is alkaline which can neutralize the acidity in the body. This study aims to determine how much iron (Fe) is dissolved in alkaline water. The initial stage of this research is to obtain data on people who consume alkaline water as their daily drinking water. Furthermore, the sampling used purposive sampling method, based on the sample criteria, namely alkaline water treatment which sourced from well water, rain water and PDAM water. The last step is to analyze the levels of iron (Fe) with laboratory tests at the Center for Environmental Health Engineering and Disease Control Class 1 Makassar. The time of the study began in July 2022. The sample of this study was taken as many as 3 samples. This research method uses an Inductively Couple Plasma spectrometer to determine the level of iron (Fe) in alkaline water. Based on the laboratory tests that have been carried out, the results of the three samples did not exceed the normal limit set by the Minister of Health, namely 0.3 mg/L.